Thermo-Economic Evaluation of gas turbine plant with inlet air cooling: UBARI case study - Zakareia A. Alarabi; Altaher O. Alreda; Abduesslam. A. Maki; Tarek. M. Khalifa (African Journal of Advanced Pure and Applied Sciences, 2022)
The efficiency of gas turbines is influenced by the climate conditions, The power output of gas turbines drops to a level that is less than estimated under high temperature and dry conditions which occur in UBAREI through the hot seasons, Atmospheric air temperature can be cooled by several cooling systems, for example, an evaporative cooler or an absorption chiller. This paper simulated thermodynamically the performance of the gas turbine unit at the site of UBARI (latitude 26.58 N º) Located around 1,000 km south of Tripoli city. This investigation was conducted for the SGT 2000 The thermodynamic equations of the suggested gas turbine model were solved using THERMOFLEX software. The results were obtained to study the thermal performance and economic analysis of the gas turbine unit without a cooling system, and compare them with the performance of each gas turbine unit equipped with an evaporative cooler and another equipped with an absorption cooler, Studied gas turbine parameters are power output, thermal efficiency, and heat rate. The results showed that at atmospheric air temperature equal to 313 K the evaporative cooler system provides an augmentation of 8.75% in power output and 2.6% in thermal efficiency. While an absorption chiller, system can achieve an increase of 13.58 % in power output and 3.5% in thermal efficiency.